Interface characterization of B4C‐based multilayers by X‐ray grazing‐incidence reflectivity and diffuse scattering. (20th March 2013) - Jiang, Hui; Wang, Zhanshan; Zhu, Jingtao
<x xml:space="preserve">Abstract</x> B4C‐based multilayers have important applications for soft to hard X‐rays. In this paper, X‐ray grazing‐incidence reflectivity and diffuse scattering, combining various analysis methods, were used to characterize the structure of B4C‐based multilayers including layer thickness, density, interfacial roughness, interdiffusion, correlation length, etc. Quantitative results for W/B4C, Mo/B4C and La/B4C multilayers were compared. W/B4C multilayers show the sharpest interfaces and most stable structures. The roughness replications of La/B4C and Mo/B4C multilayers are not strong, and oxidations and structure expansions are found in the aging process. This work provides guidance for future fabrication and characterization of B4C‐based multilayers.